Narrative approach to understanding compassion: a mixed methods study in a Polish sample - Zieba, Mariusz; Zatorski, Mateusz P.; Wójcik, Natalia E. (Frontiers in Psychology, 2025)
ObjectivesThis study investigates the relationship between compassion, defined by Gilbert as “a sensitivity to suffering in self and others, with a commitment to try to alleviate and prevent it” and narrative identity. We explored whether individuals with high and low levels of compassion differ in narrative characteristics such as affective tone, agency, and communion themes, as well as the use of redemption or contamination sequences in stressful life event narratives.MethodsA mixed-method study was conducted with Polish adult participants (N = 63), half of whom had low and the other half high levels of compassion. Participants completed several questionnaires, including the Compassion Action and Engagement Scale. A few weeks later, they participated in individual interviews where they narrated several key life events. The interviews were recorded, transcribed, and coded by an individual blind to the participants' compassion levels and other identifying information. The self-narratives were analyzed for affective tone, agency and communion themes, and redemption and contamination sequences. Differences in these elements between individuals with low and high compassion were analyzed using t-tests.ResultsOur findings indicate that individuals with higher compassion more frequently incorporate themes of agency and communion in their narratives, particularly in stories of failure and the past year's most difficult event. The narrative identity of a highly compassionate person includes more content related to seeing oneself as sensitive to suffering and actively working to reduce or prevent it.ConclusionsThis study highlights how individuals with varying levels of compassion construct narratives about significant life events. Narrative approaches can foster compassionate engagements and actions, potentially improving therapeutic practices and personal development strategies. The results underscore the importance of narrative analysis in understanding compassion and suggest that compassion levels may influence how individuals interpret and narrate their life experiences, offering valuable insights for future research.